Assessment of the effects of low molecular heparins in pulmonary embolism prophylaxis - Michał Piwoński; Klaudia Żak; Piotr Piech; Małgorzata Neścior (Kazimierz Wielki University, 2019)
Introduction: Pulmonary embolism (PE) is a severe condition that can be the source of significant morbidity and mortality. It is the major complication of venous thromboembolism (VTE) which, by occluding the pulmonary arterial bed may lead to an acute life-threatening state. The clinical management of patients with acute pulmonary embolism has rapidly changed over the years. After the diagnosis of the PE, the anticoagulant and thrombolytic therapy is initiated. Most commonly, low molecular weight heparins (LMWH), unfractionated heparins (UFH), fondaparinux or vitamin K antagonists are used for the anticoagulant therapy. However, LMWH are still uncertain agents, both in the PE prophylaxis and in the high-risk PE cases. Objective: The aim of the article is to assess the effects of LMWH in the pulmonary embolism prophylaxis. State of knowledge: A range of clinical and epidemiological studies have shown the relationship between the anticoagulant therapy using the LMWH in the PE prophylaxis. Lower risk of not only PE but also therapy-induced haemorrhages, blood clots and embolisms recurrences were proven in several meta-analyses. Moreover, the LMWH therapy seems to have a better impact on prevention of VTE symptoms and post-surgical embolisms than other anticoagulant agents. However, some studies have shown that the therapy using LMWH can be replaced with another anticoagulant with a comparable risk of complications. Conclusion: In the light of this informations, it is surely possible that the LMWH has a better impact in the PE prophylaxis and post-surgical complications prevention than other agents. Still, we can face various results of the studies but the effectiveness of their activity in most cases leaves no doubt for the reasonableness of their usage.